Pengaruh Salinitas Pasir Terhadap Kuat Tekan Bata - Mascik, Deny perayuda; S Suzen, Zaldy; Ary W, Ilham (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The development of technology, especially in the construction field, in manufacturing bricks is increasingly rapid and varied, one of which is lightweight brick. The light brick is a composite building material made of sand, cement, limestone, gypsum, water, and aluminum powder. In general, lightweight bricks have two types, Autoclaved Aerated Concrete (AAC) and Cellular Lightweight Concrete (CLC). Light bricks were created to lighten the structural load of a construction building, speed up construction, and minimize material waste during the wall installation process. Sand is a staple in the construction process. In addition, sand material cannot be separated from its use in the industrial world. The Taguchi method is a methodology in engineering that aims to improve the quality of products and processes and can reduce costs and resources to a minimum. The compressive strength of the concrete load is the magnitude of the load per unit area, which causes the concrete specimen to collapse when loaded with a specific compressive force, which is generated by the press machine; the compressive strength of the concrete will increase with increasing age of the concrete, where the compressive strength of the concrete will increase rapidly (linearly). Salinity is the salt content dissolved in water which is one of the physical parameters that can affect the quality of water, soil and sand.